The role of landscape evolution in the genetic diversification of a stream fish Sarcocheilichthys parvus from Southern China - Li, Mingyue; Yang, Xishu; Ni, Xiaomin; Fu, Cuizhang (Frontiers in Genetics, 2023)
Sarcocheilichthys parvus (Cypriniformes: Gobionidae) is a stream fish which is endemic to sub-tropical coastal drainages in southern China, thus offering a valuable model for understanding how genetic divergence arises in stream-adapting freshwater fishes in this region. Using the mitochondrial Cyt b gene, integrative analyses of phylogeny, population demography, and ancestral area and paleo-drainage reconstructions are carried out to explicitly explore the role of landscape evolution in genetic diversification of S. parvus. The time-calibrated phylogeny of S. parvus indicates the splitting of two major lineages (A and B) at ~3.66 Ma. Lineage A inhabits the Poyang Lake sub-drainage of the middle Yangtze River, Han River, and Pearl River, and can be split into two sub-lineages (A-I and A-II), where sub-lineage A-II can be further sub-divided into three infra-sub-lineages (A-IIa, A-IIb, and A-IIc). Except for the infra-sub-lineage A-IIc, which is restricted to the Han River and Pearl River, the other sub-lineages and infra-sub-lineages live exclusively in the Poyang Lake sub-drainage. Lineage B lives in the lower Yangtze River, Qiantang River, Jiaojiang River, and Ou River, displaying close genetic relationships among the drainages. Rapid population expansion has occurred since the Late Pleistocene. Our findings indicate that the splitting of lineages A and B could be attributed to geographic isolation due to the Zhe-Min Uplift, acting as a biogeographic barrier before the late Early Pleistocene. Furthermore, the strong genetic divergence within Lineage A could be explained by stream capture and Poyang Lake acting as an ecological barrier; while the lack of phylogenetic structure within Lineage B may have been the result of paleo-drainage connections or episodic freshwater connections during the eustatic low stand of sea level in the late Middle–Late Pleistocene.